The connexin 43 C-terminus: A tail of many tales - Leithe, Edward; Mesnil, Marc; Aasen, Trond (Biochimica et biophysica acta, 2018)
Connexins are chordate gap junction channel proteins that, by enabling direct communication between the cytosols of adjacent cells, create a unique cell signalling network. Gap junctional intercellular communication (GJIC) has important roles in controlling cell growth and differentiation and in tissue development and homeostasis. Moreover, several non-canonical connexin functions unrelated to GJIC have been discovered. Of the 21 members of the human connexin family, connexin 43 (Cx43) is the most widely expressed and studied. The long cytosolic C-terminus (CT) of Cx43 is subject to extensive post-translational modifications that modulate its intracellular trafficking and gap junction channel gating. Moreover, the Cx43 CT contains multiple domains involved in protein interactions that permit crosstalk between Cx43 and cytoskeletal and regulatory proteins. These domains endow Cx43 with the capacity to affect cell growth and differentiation independently of GJIC. Here, we review the current understanding of the regulation and unique functions of the Cx43 CT, both as an essential component of full-length Cx43 and as an independent signalling hub. We highlight the complex regulatory and signalling networks controlled by the Cx43 CT, including the extensive protein interactome that underlies both gap junction channel-dependent and -independent functions. We discuss these data in relation to the recent discovery of the direct translation of specific truncated forms of Cx43. This article is part of a Special Issue entitled: Gap Junction Proteins edited by Jean Claude Herve. •The Cx43 C-terminus (CT) is fundamental for correct function of Cx43 gap junctions.•The Cx43 CT is highly regulated post-translationally, e.g. by phosphorylation.•The Cx43 CT endows Cx43 with unique isoform-specific functions.•The Cx43 CT interacts with many proteins and have channel-independent functions.•Truncated forms of Cx43 containing the CT can be synthesized independently.